Study protocol for the Flooring for Injury Prevention (FLIP) Study: a randomised controlled trial in long-term care. Issue 6 (4th April 2016) - Lachance, Chantelle C; Feldman, Fabio; Laing, Andrew C; Leung, Pet Ming; Robinovitch, Stephen N; Mackey, Dawn C
Abstract : Background: A promising strategy for reducing the incidence and severity of fall-related injuries in long-term care (LTC) is to decrease the ground surface stiffness, and the subsequent forces applied to the body parts at impact, through installation of compliant flooring that does not substantially affect balance or mobility. Definitive evidence of the effects of compliant flooring on fall-related injuries in LTC is lacking. The Flooring for Injury Prevention (FLIP) Study is designed to address this gap. Methods: The FLIP Study is a 4-year, parallel-group, 2-arm, randomised controlled superiority trial of flooring in 150 resident rooms at a LTC site. The primary objective is to determine whether compliant flooring reduces serious fall-related injuries relative to control flooring. Intervention (2.54 cm SmartCells compliant; 74 rooms) and control (2.54 cm plywood; 76 rooms) floorings were installed over the top of existing concrete floors and covered with identical 2.00 mm vinyl. The primary outcome is serious fall-related injury, defined as any impact-related injury due to a fall in a study room that results in Emergency Department visit or hospital admission. Secondary outcomes include minor fall-related injury, any fall-related injury, falls, number of fallers, fractures, and healthcare utilisation and costs for serious fall-related injuries. Randomisation of study rooms, and residents in rooms, was stratified by residential unit, and flooring assignments were concealed. Outcome ascertainment began September 2013. Discussion: Results from the FLIP Study will provide evidence about the effects of compliant flooring on fall-related injuries in LTC and will guide development of safer environments for vulnerable older adults. Trial registration number: NCT01618786.